2022
DOI: 10.1002/smm2.1084
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth of ultrathin ferromagnetic β‐MnSe semiconductor

Abstract: Two-dimensional (2D) magnetic crystals with intrinsic ferromagnetism are highly desirable for novel spin-electronic devices. However, the controllable synthesis of 2D magnets, especially the direct growth of 2D magnets on substrate surfaces, is still a challenge. Here, we demonstrate the synthesis of ultrathin zinc-blende phase manganese selenide (β-MnSe) nanosheets using the chemical vapor deposition (CVD) technique. The 2D β-MnSe crystals exhibit distinct ferromagnetic properties with a Curie temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Finally, we discuss the applicability of such a spin-filtering system to two-dimensional materials, which are the promising candidates for future opto-electronic and spintronic devices. 37 For transition metal dichalcogenides (TMDCs) such as MoS 2 38 and WS 2 , 39 spin polarization of the optically excited carries higher than 60% has been observed at RT via circularly polarized PL spectroscopy. It has recently been reported in these materials that deep-level defects can be introduced in the band gap.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we discuss the applicability of such a spin-filtering system to two-dimensional materials, which are the promising candidates for future opto-electronic and spintronic devices. 37 For transition metal dichalcogenides (TMDCs) such as MoS 2 38 and WS 2 , 39 spin polarization of the optically excited carries higher than 60% has been observed at RT via circularly polarized PL spectroscopy. It has recently been reported in these materials that deep-level defects can be introduced in the band gap.…”
Section: Resultsmentioning
confidence: 99%
“…3(b) and 3(c). [39,40] Here, 𝛽-MnSe nanosheets exhibited distinctive ferromagnetism with Curie temperature of only 42.3 K. On the other hand, 𝛼-MnTe is a room-temperature antiferromagnetic, direct-band-gap p-type semiconductor, possessing a unique band structure. Yuan et al reported the growth of highly stable ultra-thin 𝜀-phase iron oxide crystals in ambient air.…”
Section: -3mentioning
confidence: 92%
“…Consequently, researchers have turned to the CVD method for epitaxial growth of materials such as MnSe, MnTe, Cr5Te8, and Cr2S3 on mica or sapphire substrates. [22,[39][40][41] In comparison to molecular beam epitaxy, which suffers from drawbacks such as expensive equipment, complex procedures, and low growth efficiency, CVD offers a more straightforward and practical approach. Te atoms in the film.…”
Section: Reviewmentioning
confidence: 99%
“…However, higher flow rate of H 2 leads to increase of the diffusion rate of Mn and Se providing sufficient precursor to create more complicated structure. In addition, during the formation of complex structure in rich H 2 environment, Mn terminated edge growth becomes more energetically favorable [57].…”
Section: Chemical Vapor Deposition (Cvd) Chemical Vapor Deposition (C...mentioning
confidence: 99%